Continuous Users of Long-Term Care 2.0 Plan in Taiwan: Patterns and Health Costs Over Time - Shih-Cyuan Wu; Ya-Mei Chen; Shiau-Fang Chao; Ming-Jen Lin; Chien-Fang Chu (Journal of Applied Gerontology, 2026)
Background Older adults exhibit substantial heterogeneity in long-term care needs, yet evidence remains limited on how different patterns of home- and community-based service utilization are associated with healthcare costs across disability levels. Objective To examine the associations between patterns of home- and community-based service utilization and healthcare cost trajectories among older adults with varying levels of disability. Methods We analyzed nationwide administrative data from Taiwan’s Long-Term Care Plan 2.0 linked with National Health Insurance claims from 2018 to 2020. Latent class analysis identified distinct service utilization patterns. Generalized estimating equations were used to estimate monthly healthcare costs over a 1-year follow-up period, stratified by disability level. Results Five distinct service utilization patterns were identified. Integrated personal and medical care was associated with more favorable healthcare cost trajectories, particularly among older adults with moderate or severe disability, whereas more fragmented service patterns were associated with higher inpatient costs.